Diversity and inclusion in sport organizations : a multilevel perspective - Cunningham, George B. (London, United Kingdom : Routledge, 2019)
Diversity and inclusion in sport organizations" is a comprehensive introduction to the ways in which people differ - including race, sex, age, mental and physical ability, appearance, religion, sexual orientation, and social class - and the importance of these differences for sport organizations. It offers strategies for managing diversity in work and sport environments and provides an overview of diversity training that can be implemented in the workplace.
PART I: FOUNDATIONS OF DIVERSITY AND INCLUSION -- 1. Overview of Diversity and Inclusion -- 2. Theoretical Tenets of Diversity and Inclusion -- 3. Bias -- PART II: FORMS OF DIVERSITY -- 4. A Framework to Understand Diversity Forms -- 5. Race -- 6. Gender -- 7. Age -- 8. Disability -- 9. Weight -- 10. Religion -- 11. Sexual Orientation, Gender Identity, and Gender Expression -- 12. Social Class -- PART III: CREATING AND SUSTAINING INCLUSIVE SPORT ORGANIZATIONS -- 13. Strategies for Inclusion -- 14. Diversity Training -- 15. Change and Inclusion Through Sport.
Includes bibliographical references and index.
Keywords: SPORTS ADMINISTRATION -- UNITED STATES